Remote sensing of water vapour in Venus' middle atmospere - Koukouli, M; Koukouli, Mary Elizabeth (2002)
﻿ The Pioneer Venus Orbiter Infrared Radiometer and Venera 15 Fourier Transform Spectrometer observations of thermal emission from Venus' middle atmosphere between 10°S and 50°N were used to determine global maps of temperature, cloud optical depth and water vapour abundance. The spectral regions observed include the strong 15 μtm carbon dioxide band and the 45 μm fundamental rotational water band. The main aim of this thesis is to reconcile the water vapour abundance results from these two sets of observations reported in previous studies. New radiative transfer and retrieval models have been developed for this purpose based on new correlated-k absorption tables calculated with up-to-date spectral line data. The H2SO4 cloud opacity and scattering properties have been recalculated from new refractive index data using Mie theory. For the first time these two sets of observations have been analysed using the same retrieval tools. From the Pioneer Venus Orbiter Infrared Radiometer observations we report a high abundance of water vapour in the early afternoon at the equatorial cloud-top region and a strong day-night variability in the cloud-top pressure. From the Venera 15 Fourier Transform Spectrometer observations we report medium local variability in water vapour abundance, with highest values in the near-equatorial region and slight decrease towards the polar region. It is found that serious constraints are placed on the validation of the retrievals by the lack of adequately accurate H2SO4 optical properties data in the shorter wavelengths and by the poor vertical resolution when sensing the complex but interesting cloud region which prohibits its rigorous modelling. The proposed European Space Agency Venus Express mission will carry a number of high resolution infrared and UV instruments that will shed new light to the interesting question of water vapour abundance in Venus' middle atmosphere.